Land Subsidence Policy in the Context of Good Governance Principles (Comparing Indonesia and Japan) - Herlambang, Pratama Herry; Utama, Yos Johan; Putrijanti, Aju; Prayogo, Silvan Susanto (Lex Scientia Law Review, 2023)
Land subsidence poses a significant environmental challenge globally, fueled mainly by anthropogenic activities such as excessive groundwater extraction, rampant overdevelopment, and alterations in soil geological structures. This issue has far-reaching consequences, including infrastructure deterioration, heightened flood vulnerabilities, and severe threats to both the environment and local communities. The city of Jakarta, Indonesia, has experienced a particularly pronounced impact from land subsidence since the 1980s. This study delves into the governmental responses of Indonesia and Japan to address the complex problem of land subsidence, emphasizing their adherence to principles of good governance, including transparency, accountability, and community engagement. The analysis scrutinizes various aspects of policy development, stakeholder participation, funding mechanisms, technological innovations, and the overall efficacy of these measures in mitigating land subsidence. Through a comparative lens, the research seeks to unearth effective strategies and successful policy implementations in both nations. The methodology employed adopts a normative approach, scrutinizing concepts, norms, principles, legal frameworks, and ethical considerations associated with land subsidence policies within the context of good governance. This research contributes to a holistic comprehension of land subsidence management, providing valuable insights into the effectiveness of policies aimed at addressing this critical environmental challenge.